Pilot Plant Study on the Extractive Distillation of Toluene-Methylcyclohexane Mixtures Using Nmp and the Ionic Liquid [Hmim][Tcb] as Solvents - Quijada-Maldonado, E (Elsevier B.V., 2016)
The separation of the close-boiling point mixture: toluene - methylcyclohexane can be carried out by extractive distillation using the ionic liquid 1-hexyl-3-methylimidazolium tetracyanoborate ([hmim][TCB]), reported as promising solvent for the separation of this mixture. However, the polar nature of ionic liquids causes the formation of two liquid phases which can be overcome with high solvent-to-feed ratios (S/F) resulting in high liquid phase viscosities that cause mass transfer limitations. Experiments in an extractive distillation pilot plant were performed with the objective of firstly exploring different operating conditions and secondly to compare the mass transfer efficiencies produced by [hmim][TCB] and the reference organic solvent N-methyl-2-pyrrolidone. Pure viscosity, density and surface tension data as well as ternary viscosity and density data of tolune - methylcyclohexane - [hmim][TCB] were measured to compute the mass transfer efficiency. From pilot plant experiments it was found that all the studied operating conditions did not form two-liquid phases. However, the high solvent-to-feed ratios increased the liquid phase viscosities and consequently the use of this ionic liquid produces Height Equivalent to a Theoretical Plates (HETPs) twice as high as the reference solvent NMP causing slightly lower top purities and a longer required distillation column for a required separation. © 2016, Elsevier B.V. All rights reserved.